Child feeding practices in rural Ethiopia show increasing consumption of unhealthy foods - Woinshet Tizazu; Arnaud Laillou; Kalle Hirvonen; Stanley Chitekwe; Kaleab Baye (Wiley, 2024)
Abstract The quality of complementary feeding can have both short‐ and long‐term health impacts by delaying or promoting child growth and establishing taste preferences and feeding behaviours. We aimed to assess the healthy and unhealthy feeding practices of infants and young children in rural Ethiopia. We conducted two rounds of surveys in December 2017/18 in Habru district, North Wello, rural Ethiopia among caregivers of infants and young children (N = 574). We characterised the consumption of infants and young children using non‐quantitative 24 h recall and the World Health Organization infant and young child feeding indicators. Sociodemographic characteristics, anthropometry and haemoglobin concentrations were assessed. Breastfeeding was a norm as 82% and 67% were breastfed in the first and second rounds. Between the two rounds, dietary diversity increased from 5% to 17% (p < 0.05), but more pronounced increases were observed in the consumption of ultra‐processed food (UPFs). Up to one‐in‐five (22%) of the children consumed UFPs. With an average of only three food groups consumed, the consumption of nutrient‐dense foods like animal source foods, fruits and vegetables was very low particularly among younger children. UPFs are an additional risk factor that contributes to poor quality diets. Behavioural Change Communication interventions, including those in rural areas, should explicitly discourage the consumption of UPFs. Future studies should aim to quantify the amount of UPFs consumed and evaluate how this is associated with diet adequacy and nutritional outcomes.